Adaptation of shift work schedules for preventing and treating sleepiness and sleep disturbances caused by shift work - Erren, T.; Herbst, C.; Koch, M.; Fritschi, Lin; Foster, R.; Driscoll, T.; Costa, G.; Sallinen, M.; Liira, J. (John Wiley & Sons, Ltd., 2013)
© 2013 The Cochrane Collaboration. This is the protocol for a review and there is no abstract. The objectives are as follows: To assess the effects of adaptation of shift schedules for preventing and treating sleeping and alertness problems in shift workers.